Brown planthopper honeydew-associated symbiotic microbes elicit momilactones in rice - Wari, David (Plant Signal Behav, 2019)
Plants use many natural products to counter pests and diseases in nature. In rice, direct defense mechanisms include broad range of secondary metabolites, such as phenolamides (PA), diterpene phytoalexins, and flavonoid sakuranetin. Recently, accumulation of PAs in rice was shown to be under control of microbial symbionts in honeydew (HD), digestive waste from the rice brown planthopper (Nilaparvata lugens; BPH), but whether HD microbiota can also promote diterpene phytoalexins, momilactone A (MoA) and MoB, has not been reported. Here, we demonstrate that crude HD, but not a filtered one, induces MoA and MoB in rice, suggesting the involvement of BPH-HD endosymbionts. Consequently, microbial strains previously isolated from HD could promote MoA and MoB levels in wounded rice leaves, suggesting that rice indeed responds to BPH by cumulative chemical defense that involves both PA and diterpene phytoalexin pathways.